Disturbed regulation of immunothrombosis in cerebral ischemia associated with SARS-CoV-2 infection - Plem, Richard; de Buhr, Nicole; Imker, Rabea; Akhdar, Silke; Meurer, Marita; Falk, Christine S.; Ernst, Johanna; Gabriel, Maria M.; Keil, Jana; Kopfnagel, Verena; Illig, Thomas; Weissenborn, Karin; et al. (Frontiers in Immunology, 2026)
BackgroundDuring the COVID-19 pandemic, it became evident that an infection with SARS-CoV-2 is associated with an increased predisposition for thrombembolic events. Recent studies suggest an excessive neutrophil extracellular trap (NET)-formation in response to SARS-CoV-2, which is considered a hallmark in immunothrombosis. A better understanding of the (dys)regulation of NET-formation in COVID-19 may provide the basis for new therapeutic strategies.MethodsWe conducted a pilot study with a total of 84 patients in three groups matched in a 1:1:1 fashion: Group 1: patients with acute ischemic stroke (AIS) or transient ischemic attack (TIA) and SARS-CoV-2 infection, Group 2: patients with AIS and no SARS-CoV-2 infection and Group 3: patients with SARS-CoV-2 infection and no AIS or TIA. Venous blood samples were collected from all patients and subsequently analyzed for NET-specific markers, NET regulators (Deoxyribonuclease (DNase) activity) and a panel of cytokines.ResultsCitrullinated histone3 (H3cit) and elastase levels were higher in groups with SARS-CoV-2 infection (Groups 1 and 3) compared to patients without ((group 1: H3cit = 2.9 (1.11–6.89) ng/mL, elastase = 312.1 (162–435.4) ng/mL and group 3: H3cit = 3.31 (2.03–7.97) ng/mL and elastase = 433.1 (281–783.8) ng/mL) vs. group 2: H3cit = 1.17 (0.61–2.15) ng/mL), elastase = 195.1 (91.99–386.9) ng/mL). No relevant differences were found regarding other measured NET-marker (myeloperoxidase, LL-37). DNase activity was lower in group 1 (6.12 (4.97–6.78) pmol/mL/min) compared to both other groups (group 2: (7.16 (5.88–7.85) pmol/mL/min) (p=0.018) and group 3 (7.19 (5.52–8.54) pmol/mL/min) (p=0.013).ConclusionThis pilot data suggest that a disturbed regulation of NETs in patients with SARS-CoV-2 infection may play a role in SARS-CoV-2 associated cerebral ischemia. These results highlight the importance of further investigating the role of NETs in immunothrombosis in the context of viral infections, to better understand its potential as a target for therapeutic strategies.